Moving from Vatican Bling to Malchus's Ear: Taking the "Catholic Imagination" Seriously When Thinking About Catholic Devotions in Centuries Past. - CARROLL, MICHAEL P. (Logos: A Journal of Catholic Thought & Culture)
The article offers information on "Heavenly Bodies: Fashion and the Catholic Imagination" in Metropolitan Museum of Art in New York City in 2018. It mentions that exhibition displayed secular clothing by leading fashion designers that had been inspired by religious dress and religious art and secular designs that had been inspired by sacred art.